Single-cell sequencing reveals the response mechanisms of vascular endothelial cells to glucocorticoids in diabetic retinopathy - Lingda Wang; Rong Zhang; Lin Wang; Yongrui Wang; Xiaodan Zhang; Guohong Zhou (PLoS ONE, 2025)
Background One serious consequence of diabetes mellitus is diabetic retinopathy (DR), which impairs eyesight to the point of blindness. While glucocorticoid medications are commonly employed in the management of DR, their therapeutic efficacy requires enhancement. Due to the tight association between glucocorticoid-related genes and the onset and development of DR, a comprehensive examination of its root cause of activity may be able to overcome the drawbacks of existing treatment approaches. Methods R programming tools were used to examine the single-cell RNA sequencing (scRNA-seq) dataset GSE178121, which was obtained from the Gene Expression Omnibus (GEO) database. To evaluate glucocorticoid activity, a gene set related to glucocorticoid phenotypes was sourced from the Molecular Signatures Database (MSigDB), followed by the identification of key cellular populations within DR tissues. Subsequently, these key cells underwent pseudotime analysis, transcription factor (TF) evaluation, cell-cell communication assessment, differential gene screening, and the construction of a regulatory network. Results Our investigation demonstrated that vascular endothelial cells (VECs) in DR tissue exhibited markedly elevated glucocorticoid activity. KLF4 is among the TFs that are intimately linked to the onset of DR, and hydroxyurea could be a beneficial medication. Cell-cell communication analysis highlighted the PTN and ANGPTL signaling pathways as important signaling pathways in DR. In the meanwhile, we identified 25 Hub genes, including DUSP6 , AP1S2 , and PTPRB , which were verified to be differentially expressed in DR. Conclusion In conclusion, our comprehensive study elucidated the complex interactions of glucocorticoids in the pathogenesis of DR, thereby revealing potential signaling pathways and therapeutic targets.